(untitled) (Palimpsesto, 2020)
This paper explores Eco Contemporáneo, an Argentine journal founded and directed by Miguel Grinberg, with thirteen issues published between 1961 and 1969. The main objective is to detect lines of continuity between Thomas Merton’s letters and contributions to the journal and Eco’s ideological and cultural program. In this way, we aim to contribute to the study of networks formed by these two cultural actors of the 1960s who, together with other writers and intellectuals from North and South America conducted gatherings, publications and projects that would define the decade’s American image from a literary, cultural, ideological and political perspective.